PENERAPAN APLIKASI SURAT MASUK SURAT KELUAR (SUMAKER) SEBAGAI MEDIA DIGITAL DI KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAM SUMATERA SELATAN - SRI AGUSTINI; Sonia Nurprameswari (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Politik Universitas Islam Negeri Raden Fatah Palembang, 2022)
The development of technology that is growing rapidly as it is today has resulted in many changes in everyday human life that make it much easier. The existence of electronic mail is an example of the development of communication technology, electronic mail can help the process of sending letters become easier and faster, one example is the SISUMAKER application at the Ministry of Law and Human Rights of the Republic of Indonesia. The research method uses a descriptive qualitative approach by using case study research through observation, interviews, and documentation. The results of this study are focused on the important role of an electronic mail application in this agency environment so that the correspondence system becomes more effective and efficient in achieving goals in the office environment itself. The organizational communication process that takes place is the upward, downward, horizontal and cross communication pattern to be able to support a good work process among employees through SISUMAKER. However, the SISUMAKER application still makes the paperwork ineffective and efficient because the employees who handle the application are not optimal. The handling process in this application must be improved to make SISUMAKER make the correspondence at this agency effective and efficient.